Estudo da Potencialidade da produção de tijolos de adobe misturado com outros materiais: uma alternativa de baixo custo para a construção civil - Bouth, Jorge Alberto Cardoso (2005)
The production of the red pottery brick, made traditionally with clay, is a technique that is already stabled. However, in spite of the little complexity that involves the conventional process of these bricks production, it are exposed to many problems that begin in the fase of exploration of the mines, the problems get worse because of the lack of the clay's characterization, and they continue through the steps of the dough preparation, conformation of the products, the drying and the burning process. The wastefulness is shown and so is the low quality of the material produced. Among other factors, the high use of energy in the burning makes the cost of this material inaccessible to the low income consumer. Besides this, the destruction of the environment around the mines and the use of native vegetation to produce wood - the most used fuel in the pottery industry - make serious environmental damage. The production technique of a new type of simple brick (adobe), that has low cost and no environmental damage, can be the viable altemative to lower the cost of this part of the civil construction, and, consequently, in the building of cheaper houses. In this paper, the results of the mechanical resistance of the adobe brick are shown, using in its composition, clay, natural vegetable fibers, cement and plaster in a process that is completely handcrafted and manual. It is intented to make clear that are possible alternatives to be put in practice, with the simple process, using "raw earth" that has been used in the construction of houses in thousands of years, trying to solve these severe problems. Analysis and tests were performed to find results that could prove the possibility of the utilization of this kind of material. Other studies are in progress, and the new researches are necessary to enrich this work, but it stays the certainty that there is potential to produce bricks from adobe, as an alternative that has low cost to civil construction